Integrated AFM-Raman for molecular characterization of peptide nano- and micro-tubes - Sinjab, Faris (2015)
This work is focused on exploring a unique integration of techniques, Raman micro-spectroscopy and atomic force microscopy (AFM), which when combined offer more than the sum of their respective parts. The non-invasive chemical specificity afforded by Raman spectroscopy, combined with the nanoscale-resolution topographic imaging of AFM offer much individually. The physics underlying the practical application of each technique is very general; Raman spectroscopy detects molecular vibrational shifts using light, and AFM uses a physical probe to interact with a surface to provide topographic (and mechanical) information. As a result, there are few restrictions to the possible samples that can be studied with these techniques, from semiconductors and geological crystals, through to simple organic chemical structures all the way to complex biological molecules and systems such as cells and tissue. In this work, a synthetic biomaterial composed of diphenylalanine (FF) peptide units which self-assemble into strong tubular structures is used as a sample of interest when exploring the different possibilities available from a combined Raman-AFM instrument. First, the combined system was set up in order to perform tip-enhanced Raman spectroscopy (TERS), a technique promising Raman spectroscopic imaging at the resolution of AFM imaging. A relatively young technique, TERS has huge potential in extending the reach of Raman spectroscopic imaging to the nanoscale, at a regime where a great deal of structure exists, but is usually blurred by conventional diffraction-limited Raman microspectroscopy. A major focus in this work is addressing a current problem with TERS: the fabrication of suitable probes. TERS typically utilizes AFM tips modified to have a silver nanoparticle, capable of locally enhancing the Raman signal, attached at the probe apex. A new method is presented here that promises several improvements over existing approaches, as the entire fabrication can be performed in-situ on the instrument. Tips produced in this way are then characterized by electron microscopy and tested on FF nanotubes. Following this, several techniques for the synthesis of silver nanoparticles are explored for use in TERS. Here, the focus is particularly on decahedral nanoparticles, which can be grown into rod shaped particles with well- defined shapes and sizes. These are important considerations for obtaining the desired enhancing properties for TERS probes. Finally, the AFM-Raman instrument is used to investigate the mechanical properties of FF tubes using several methods. AFM force spectroscopy of tubes suspended across a gap can be used in conjunction with a bending beam theory to measure the Young's modulus of individual tubes. A new type of co-localized experiment using polarized Raman spectroscopy on a suspended tube under various forces from the AFM is tested, and subsequently information relating to the hydrogen bonding network is used, in conjunction with existing X-ray data, to determine the molecular contributions to the modulus using a simple model for amyloid fibrils. Each experiment operates at the single fibril level, with the same fibrils being used, such that different methods can be compared for a single FF tube.